Influência da resposta crônica sobre as variáveis hematológicas de indivíduos diabéticos tipo 2 submetidos a um treinamento misto com o uso de bola suíça - Silva, Alessandra Patrícia da (2007)
Physical exercise can be considered a health promotion instrument contributing to the immune system and providing protection against pathogens. The immune system has as its main function the defense against infection, being composed of leukocytes that modulate immune response, which can be innate or adaptive. Physical exercise can cause positive or negative changes in the total or relative number of leukocytes. When it is mild to moderate in intensity, it is considered beneficial because it improves the function of cells responsible for defense and reduces the risk of infectious diseases. On the other hand, intense and prolonged exercise can suppress the immune system, increasing the susceptibility to infections, especially in the upper respiratory tract (ITRS). Type 2 diabetes is related to an inability of the body to respond adequately to insulin, associated with resistance to insulin actions, to an abnormal but well-preserved insulin secretion and also to normal to high plasma insulin levels. Obesity, especially the distribution of fat in upper body segments and the lack of regular physical exercise are the main factors for the occurrence of type 2 diabetes in adults and children. Regular physical exercise is effective in preventing and controlling type 2 diabetes, promoting an increase in glucose assimilation and insulin sensitivity by cells. This research aimed to study the characteristics of the immune system, as well as type 2 diabetes and the relationship between the two and physical exercise. For this, the bibliographic method was used, with the analysis of works by renowned authors and other forms of publication (Internet). A group of type 2 diabetics from the Casa do Diabético de Franca was also analyzed, evaluated through a mixed physical conditioning program for upper and lower limb muscle groups, including Swiss ball exercises, over a period of 10 weeks, frequently three times a week, one hour a day, in the morning. Two blood samples were taken to prepare the hematological profile analysis before and after the training program, to compare the participants in pairs. Positive changes were found in the leukocyte subpopulations that indicate a probable improvement in the immune status. Our findings, by themselves, do not allow us to fully conclude about a possible improvement in immunological activity, which would be measured by the activation of these cells in the face of an inflammatory / infectious condition. Thus, we suggest that future studies involving experimental diabetes, induced models of infection and physical exercise be encouraged in animal models.